Accessibility Measurement for Project Prioritization in Virginia. Issue 12 (December 2019) - Hardy, Daniel; Bell, Alex; McCahill, Chris
This paper describes the accessibility scoring approach applied by the Virginia Department of Transportation (DOT) in the Smart Scale project prioritization process in 2018. The accessibility scoring approach identifies the increase in jobs accessibility for candidate projects submitted for state funding. The Smart Scale process was implemented in 2015 and entered its third round of applications in 2018; some 800 projects were evaluated during its first two years. This paper contains the following elements: an general overview of jobs accessibility as defined and measured by Virginia DOT for the Smart Scale approach; the development of the Smart Scale accessibility scoring system, including a summary of research performed to identify system parameters; the relationship between mobility and accessibility; and the Smart Scale accessibility transferability to other locations and initiatives and the possible evolution of the Virginia DOT approach in the future.